Prevalence Study of Prehypertension, Hypertension, and Risk Factors in the Adult Population in Medan, Indonesia: A Community Cross-Sectional Study - Fazidah Aguslina Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Background: Prehypertension and hypertension are serious public health issues that are frequently disregarded. The condition is linked to morbidity and is known to increase the risk of kidney, cardiovascular, and cerebrovascular illness. Objectives: The objective of this study was to determine the prevalence of pre hypertension and hypertension and factors associated among the adult population Settings and Design: This was an observational study with cross sectional design. Methods and Materials: The sample included 200 recruits from 4 subdistricts in Medan city that selected using purposive sampling. Data were collected by interviews and measurements. Statistical analysis: Data were analyzed using multiple logistic regression. Results: Prevalence of hypertension as 24.5% an hypertension as much as 34.5%. The majority of respondents were aged 45 years or younger (66.0%), 185 were female (92.5%), 124 were low income (62.0%), 143 had no family history (71.5%), 95 were overweight (47.5%), 137 were normal blood glucose, 183 had no smoking habit (91.5%), and 134 were physically inactive (67,0%). Of the Multiple Logistic regression showed that Basal metabolic index and daily vegetables and fruit consumption are significant factors contribute to prehypertenion, while age, Basal metabolic index and daily vegetables and fruit consumption are significant factors contribute to hypertension among adult population in Medan City. Conclusions: BMI and daily vegetables and fruit consumption are signifant factors to pre hypertension, while BMI and daily vegetables and fruit consumption are significant factors to hypertension among adult population. Intervention programs should be primarily focused on the risk factors such as losing weight and maintaining an ideal body weight and implementing healthy lifestyle. Keywords:  Pre Hypertension, Hypertension, Prevalence, Determinant.